Long-term Consistency in Rotavirus Vaccine Protection: RV5 and RV1 Vaccine Effectiveness in US Children, 2012–2013 - Payne, Daniel C.; Selvarangan, Rangaraj; Azimi, Parvin H.; Boom, Julie A.; Englund, Janet A.; Staat, Mary Allen; Halasa, Natasha B.; Weinberg, Geoffrey A.; Szilagyi, Peter G.; Chappell, James; McNeal, Monica; Klein, Eileen J.; et al. (Clinical infectious diseases, 2015)
Background. Using a multicenter, active surveillance network from 2 rotavirus seasons (2012 and 2013), we assessed the vaccine effectiveness of RV5 (RotaTeq) and RV1 (Rotarix) rotavirus vaccines in preventing rotavirus gastroenteritis hospitalizations and emergency department (ED) visits for numerous demographic and secular strata. Methods. We enrolled children hospitalized or visiting the ED with acute gastroenteritis (AGE) for the 2012 and 2013 seasons at 7 medical institutions. Stool specimens were tested for rotavirus by enzyme immunoassay and genotyped, and rotavirus vaccination histories were compared for rotavirus-positive cases and rotavirus-negative AGE controls. We calculated the vaccine effectiveness (VE) for preventing rotavirus associated hospitalizations and ED visits for each vaccine, stratified by vaccine dose, season, clinical setting, age, predominant genotype, and ethnicity. Results. RV5-specific VE analyses included 2961 subjects, 402 rotavirus cases (14%) and 2559 rotavirus-negative AGE controls. RV1-specific VE analyses included 904 subjects, 100 rotavirus cases (11%), and 804 rotavirus-negative AGE controls. Over the 2 rotavirus seasons, the VE for a complete 3-dose vaccination with RV5 was 80% (confidence interval [CI], 74%–84%), and VE for a complete 2-dose vaccination with RV1 was 80% (CI, 68%–88%). Statistically significant VE was observed for each year of life for which sufficient data allowed analysis (7 years for RV5 and 3 years for RV1). Both vaccines provided statistically significant genotype-specific protection against predominant circulating rotavirus strains. Conclusions. In this large, geographically and demographically diverse sample of US children, we observed that RV5 and RV1 rotavirus vaccines each provided a lasting and broadly heterologous protection against rotavirus gastroenteritis.